Populism and Conspiracy Theory: Case Studies and Theoretical Perspectives - Butter, Michael; Hatzikidi, Katerina; Jeitler, Constanze; Loperfido, Giacomo; Turza, Lili (Taylor & Francis, 2024)
This book explores the close connections between populism and conspiracy theory. Populism and Conspiracy Theory contributes to filling the gap in the research in this area. The individual contributions in Part I provide in-depth analyses of specific configurations of populism and conspiracy theory. Part II includes nuanced considerations of more theoretical issues. The case studies cover both right-wing and left-wing manifestations of populism, while highlighting that populist movements often cut across the traditional left-right divide. Chapters focus on the twenty-first century and the first half of the twentieth century, as well as the impact of history and memory on contemporary discourses. Geographically, the case studies consider the Americas as well as Europe and Northern Africa. Theoretical discussions include the aesthetics and forms of populist conspiracism, or its dependence on new media. The disciplines represented in the volume range from political science and sociology via anthropology and history to linguistics and cultural studies. It will appeal to those interested in politics, specifically conspiracy theory, populism, democracy, and leadership. The Open Access version of this book, available at www.taylorandfrancis.com, has been made available under a Creative Commons Attribution‑Non Commercial‑No Derivatives (CC‑BY‑NC‑ND) 4.0 license